Systemic Heparinisation in Laparoscopic Live Donor Nephrectomy - Charlotte Crotty; Yasmin Tabbakh; Sarah A. Hosgood; Michael L. Nicholson (Journal of Transplantation)
Introduction. Systemic heparinisation is advocated during laparoscopic live donor nephrectomy (LDN) as a preventative measure against renal vascular thrombosis during the warm ischaemic interval. This study compares the outcome with and without the administration of systemic heparinisation. Methods. A retrospective analysis was performed on 186 consecutive LDN patients between April 2008 and November 2012. Systemic heparin (2000–3000 IU) was administered intravenously to donors (hep n=109). From January 2010, heparin was not used systemically in this group of LDN (no hep n=77). Outcome measures included donor and recipient complications, initial graft function, and 12 month graft survival. Results. The demographics of both heparinised and non-heparinised donors were similar. The warm ischaemic time (WIT) was comparable in both groups (WIT; hep 5±3 versus no hep 5±3 minutes; P=1.000). There was no difference in complication rates, no episodes of graft thrombosis, and no incidences of primary nonfunction in either group. Delayed graft function occurred in 4/109 and 1/77 (3.6% versus 1.2%; P=0.405) and there was no significant difference in graft survival (P=0.650). Conclusion. Omitting systemic heparinisation during laparoscopic donor nephrectomy is a feasible and safe approach that does not compromise donor or recipient outcome.